(untitled) (Swiss Medical Weekly, 2017)
Hyperferritinaemia is a frequent clinical problem. Elevated serum ferritin levels can be detected in different genetic and acquired diseases and can occur with or without anaemia. It is therefore important to determine whether hyperferritinaemia is due to iron overload or due to a secondary cause. The main causes of iron overload are intestinal iron hyperabsorption disorders and transfusion-dependent disorders. Iron homeostasis and iron overload are quantified by different diagnostic approaches. The evaluation of serum ferritin and transferrin saturation is the first diagnostic step to identify the cause of hyperferritinaemia. The assessment of liver iron concentration by liver biopsy or magnetic resonance imaging (MRI) may guide the further diagnostic and therapeutic workup. Liver biopsy is invasive and poorly accepted by patients and should only be carried out in selected patients with hereditary haemochromatosis. As a non-invasive approach, MRI is considered the standard method to diagnose and to monitor both hepatic iron overload and the effectiveness of iron chelation therapy in many clinical conditions such as thalassaemia and myelodysplastic syndromes. Accurate evaluation and monitoring of iron overload has major implications regarding adherence, quality of life and prognosis. There are different technical MRI approaches to measuring the liver iron content. Of these, T2 and T2* relaxometry are considered the standard of care. MRI with cardiac T2* mapping is also suitable for the assessment of cardiac iron. Currently there is no consensus which technique should be preferred. The choice depends on local availability and patient population. However, it is important to use the same MRI technique in subsequent visits in the same patient to get comparable results. Signal intensity ratio may be a good adjunct to R2 and R2* methods as it allows easy visual estimation of the liver iron concentration. In this review a group of Swiss haematologists and radiologists give an overview of different conditions leading to primary or secondary iron overload and on diagnostic methods to assess hyperferritinaemia with a focus on the role of liver MRI. They summarise the standard practice in Switzerland on the use of liver iron concentration MRI as well as disease-specific guideline recommendations.